2020
DOI: 10.1038/s42003-020-01347-9
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous L-arginine increases intestinal stem cell function through CD90+ stromal cells producing mTORC1-induced Wnt2b

Abstract: The renewal and repair of intestinal epithelium depend on the self-renewal of intestinal stem cells (ISCs) under physiological and pathological conditions. Although previous work has established that exogenous nutrients regulate adult stem cell activity, little is known about the regulatory effect of L-arginine on ISCs. In this study we utilize mice and small intestinal (SI) organoid models to clarify the role of L-arginine on epithelial differentiation of ISCs. We show that L-arginine increases expansion of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Interestingly, whether proliferation was impaired or stimulated depended on glutamate concentration 40 . L-arginine has also been shown to stimulate ISC expansion in mice 54 . Elevated activity of the amino acid sensing Target of Rapamycin (TOR) pathway, an established regulator of longevity, as a result of elevated amino acid levels may also have a role in intestinal decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, whether proliferation was impaired or stimulated depended on glutamate concentration 40 . L-arginine has also been shown to stimulate ISC expansion in mice 54 . Elevated activity of the amino acid sensing Target of Rapamycin (TOR) pathway, an established regulator of longevity, as a result of elevated amino acid levels may also have a role in intestinal decline.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to impacts on the microbiota, some amino acids may have specific roles in intestinal health maintenance. For example, increased glutamate concentration has been shown to stimulate intestinal stem cell (ISC) proliferation in Drosophila 40 and in mice 59 and L-arginine has also shown to stimulate ISC expansion in mice 60 . Beyond the gut arginine has been shown to have a positive association with lifespan in a study of fibroblasts taken from a range of primate, avian and rodent species 61 and its supplementation increases the lifespan of C. elegans 62 .…”
Section: Discussionmentioning
confidence: 99%
“…37 Arginine supplementation has been reported to alleviate intestinal damage and enhance intestinal immunity. [38][39][40] Histidine deficiency can result in intestinal epithelial cell apoptosis 41 and inflammatory response. 42 He et al found that dietary lysine enhanced villus height and crypt depth in the jejunum of weaned piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Arginine, which was enriched in the fermented-feed-treated squabs, has been reported to be an important amino acid for poultry, especially those under stress [41]. Arginine participates in the restoration of intestinal epithelial cells [42], and L-arginine can reduce intestinal mucosal injury induced by Clostridium perfringens colonization in broiler chickens [43]. Additionally, the contents of 1-arachidonoylglycerophosphoinositol, estradiol-17-phenylpropionate, aminotriazole, 3-benzoyloxy-6-oxo-12-ursen-28-oic acid, and PE (22:6/0:0) were decreased in the FMF group.…”
Section: Discussionmentioning
confidence: 99%